Functional compensators in machine drives - P. D. Balakin; V. N. Belkov; O. S. Dyundik; I. P. Zgonnik (Омский научный вестник)
Real mechanical systems are characterized by real parameters, which include primary manufacturing and assembly errors, force and temperature deformations, and abnormal operating modes, the full knowledge of which is unknown when designing systems. Incomplete knowledge about the object is compensated by using coefficients entered into calculation formulas. The coefficients form the basis of reference literature and are obtained on the basis of generalization of experience in creating objects that are similar in design and purpose. This statistical technique is used to increase the margin of safety, but it does not allow us to obtain optimal performance criteria for the design of mechanical drives in particular. It is proposed to use the principle of designing mechanical systems by giving them the property of adaptation to real parameters at the design stage. The means of adaptation is an additional motion of links to the main one, implemented in particular by functional compensators. An algorithm for the synthesis of a compensator is given on the example of the basic scheme of a friction planetary gearbox.